The Relationship Between Compensation and Motivation in the Performance of Professional Tour Guides in the Tourism Industry - Klinmuenwai, Kittisak (Local Administration Journal, 2024)
This research aimed to study the relationship between compensation and its impact on motivation in the performance of professional tour guides in the tourism industry. The study used a survey method, collecting data through a questionnaire from 400 professional tour guides. The reliability of the questionnaire was tested using Cronbach’s Alpha, yielding a value of 0.897. Descriptive statistics, including percentage, mean, frequency, standard deviation, and correlation coefficient testing, were used for data analysis. The findings revealed that professional tour guides generally had a high level of satisfaction with the compensation factors related to their duties (mean = 4.50). When analyzed by individual factors, the highest mean value was for salary (mean = 4.55), followed by overtime pay (mean = 4.52), position allowance (mean = 4.48), and welfare benefits (mean = 4.47). Furthermore, the correlation coefficient between compensation factors and motivation was positive, indicating a relationship in the same direction. The correlation coefficient between the variables was 0.018, with statistical significance at the 0.05 level.